2018
DOI: 10.1073/pnas.1805728115
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Gag-RNA interactions in HIV-1 virus assembly deciphered by single-molecule localization microscopy

Abstract: SignificanceSingle-molecule localization microscopy (SMLM) is useful for deciphering dynamic organizations of structures densely labeled by specific proteins in the cellular context with nanoscopic resolution not attainable by conventional imaging tools. Here we employed SMLM to investigate the mechanism by which the HIV-1 viral RNA (vRNA) mediates the assembly of thousands of Gag proteins into a virus particle at the plasma membrane. In contrast to the general notion that vRNA only triggers Gag assembly and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…Later on, a comparison of apparent diffusion coefficient distribution highlighted the role of the NC-RNA binding domain of Gag in HIV-1 assembly in adherent cells [71] or in CD4 T-cells [49]. Recently, studies by Floderer et al [38,48] in T cells, and Yang et al [72] in adherent cells, used sptPALM to track Gag molecules and to confirm the important role of the gRNA and the NC domain of Gag in the generation of Gag clusters at the plasma membrane of the host cell for efficient HIV-1 assembly. Floderer et al [38,48] showed that gRNA in the context of a provirus acts as a spatiotemporal coordinator of the membrane assembly process, rather than only serving as an attractor for Gag molecules to the assembly site.…”
Section: Towards a Real Time Molecular Description Of Hiv Assemblymentioning
confidence: 99%
“…Later on, a comparison of apparent diffusion coefficient distribution highlighted the role of the NC-RNA binding domain of Gag in HIV-1 assembly in adherent cells [71] or in CD4 T-cells [49]. Recently, studies by Floderer et al [38,48] in T cells, and Yang et al [72] in adherent cells, used sptPALM to track Gag molecules and to confirm the important role of the gRNA and the NC domain of Gag in the generation of Gag clusters at the plasma membrane of the host cell for efficient HIV-1 assembly. Floderer et al [38,48] showed that gRNA in the context of a provirus acts as a spatiotemporal coordinator of the membrane assembly process, rather than only serving as an attractor for Gag molecules to the assembly site.…”
Section: Towards a Real Time Molecular Description Of Hiv Assemblymentioning
confidence: 99%
“…Capsid proteins diffusing in 245 from infinity towards the growth surface must pass through a neck region with negative 246 Gauss curvature. This requirement applies even to assembly processes in which 247 RNA-protein interactions play a role [38] or proteins are targeted near capsid assembly 248 sites [39]. Consistent with this explanation is the fact that the interaction strength between the 268 capsid proteins of immature retroviruses is believed to be quite weak [42], which could 269 place them below the critical point.…”
Section: /19mentioning
confidence: 98%
“…This hole survives the pinch-off process and 36 only about 2/3 of the membrane of the completed immature HIV-1 virus is covered by 37 proteins. It is important to note that hole formation is not observed for other enveloped 38 viruses such as the Herpes and alphaviruses. Figure 1 suggests that the transport 39 current supplying proteins to the curved neck region somehow has "dried-up" before the 40 spontaneous part of the assembly could complete.…”
mentioning
confidence: 99%
“…d-A less arbitrary method is to fit all the MSD(t) curve with the MSD(t)=Dt  approximation and take benefit of numerous noisy curves to establish statistically relevant distribution of motion, allowing to qualitatively classify the type of motion observed in the cell. This technique has been used to observe directed motion close to the assembly site in [58]. e-A more rigorous analysis aims at disentangling the part of Brownian and directed motion in the trajectory using the Langevin equation of motion.…”
Section: Towards a Real Time Molecular Description Of Hiv Assembly Inmentioning
confidence: 99%